On a viscoelastic plate equation with a polynomial source term and p(x,t)-Laplacian operator in the presence of delay term - Merah, Ahlem; Mesloub, Fatiha (Journal of Innovative Applied Mathematics and Computational Sciences, 2022)
In this paper, the blow-up of solutions for a Dirichlet-Neumann problem to initial nonlinear viscoelastic plate equation with a lower order perturbation of p(x,t)-Laplacian operator in the presence of time delay is obtained. Under suitable conditions on g and the variable exponent of the p(x,t)-Laplacian operator, we prove that any weak solution with nonpositive initial energy as well as positive initial energy blows up in a finite time.